The Evaluation of Online and Face to Face Physical Education Learning Policy at Elementary School Level - Baidowi, Ach. (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
The wide spread of Covid-19 virus in Indonesia enforced the temporary closure of education process followed by the remote learning regulation for all levels of education. The aim of the study was to evaluate the process of online and face to face learning by using the evaluation stage from Edward A. Schuman through a qualitative approach. The data were collected by conducting observation, documentation, and interview of four Physical Education, Sport, and Health teachers, students grade 4-6, class teachers, and parents. The results of the study showed that (1) the purpose was to prevent the spread of Covid-19 virus and to provide a maximum education service. (2) The problems faced in the face to face learning included the lack of tools, time constraint, the lack of practice, the unreachable goals, and the lack of supervision. Meanwhile, the problems faced in the online learning included the lack of media, the lack of signal, no practice was conducted, and the teachers did not use the method. (3) The activities in a face to face learning included visiting students’ houses, while the activities in online learning included using a smartphone and social media. (4) The changes included accessing a wide material, understanding IT, lack of motivation, lack of enthusiasm, the decrease in understanding, and the high use of lecturing method. (5) The changes occurred as the result of the online and face to face learning processes. The results conclude that, based on the problems faced and negative changes perceived by students and teachers, the online and face to face learning are less effective to be conducted for a long period of time. The implication of this study was for the betterment of the instructional process and educational policy.